2018
DOI: 10.1186/s12884-018-1749-6
|View full text |Cite
|
Sign up to set email alerts
|

They receive antenatal care in health facilities, yet do not deliver there: predictors of health facility delivery by women in rural Ghana

Abstract: BackgroundResearch has shown that use of antenatal services by pregnant women and delivery in health facilities with skilled birth attendants contribute to better delivery outcomes. However, a gap exists in Ghana between the use of antenatal care provided by health facilities and delivery in health facilities with skilled birth attendants by pregnant women. This study sought to identify the predictors of health facility delivery by women in a rural district in Ghana.MethodsThis was a cross-sectional study cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
56
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 37 publications
19
56
2
Order By: Relevance
“…Parity was shown to have negatively in uenced the uptake of maternal health care services (11,12,19). Contrary to these reports, in our work, it is rather age of the mother that had a signi cant association with the type of the trajectory.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Parity was shown to have negatively in uenced the uptake of maternal health care services (11,12,19). Contrary to these reports, in our work, it is rather age of the mother that had a signi cant association with the type of the trajectory.…”
Section: Discussioncontrasting
confidence: 99%
“…Religion is considered to have an in uence over maternal healthcare utilization in some recent studies (10)(11)(12)19). However, the relationship is best understood with the present study as our nding shows the point where religion stimulates and fails to stimulate maternal healthcare utilization.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Also, four variables (number of antenatal visits, timing of antenatal visits, healthcare decision, and perception of whether or not distance to facility is a big problem to accessing healthcare) were selected for statistical control in the study. A number of studies have found antenatal care visits and timing to have significant association with institutional delivery [54][55][56][57][58], while healthcare decision which proxy women's status, and perception of distance were included in line with the causes of the second delay in the theoretical underpinning of the study [34]).…”
Section: Explanatory and Control Variablesmentioning
confidence: 99%
“…30 Further, reproductive health characteristics such as parity and prior facility delivery may positively or negatively impact a woman's likelihood of returning to facilities, based on experiences with the health system. 31,32 Lastly, we collected first ANC visit facility location to address potential area-level variance on the likelihood of facility delivery.…”
Section: Data Collection and Study Variablesmentioning
confidence: 99%